2023
DOI: 10.1136/bmj-2022-072249
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal gestational weight gain and neonatal outcomes in low and middle income countries: individual participant data meta-analysis

Nandita Perumal,
Dongqing Wang,
Anne Marie Darling
et al.

Abstract: Objective To estimate the associations between gestational weight gain (GWG) during pregnancy and neonatal outcomes in low and middle income countries. Design Individual participant data meta-analysis. Setting Prospective pregnancy studies from 24 low and middle income countries. Main outcome measures Nine neonatal outcomes related to timing (preterm birth) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 114 publications
(266 reference statements)
1
6
0
Order By: Relevance
“…Gestational weight gain (GWG) has been shown to be associated with macrosomia and large for gestational age (LGA) infants [ 10 , 11 ]. Individual participant data from a meta-analysis revealed that excessive gestational weight gain (EGWG) was related to a greater risk of macrosomia (RR = 1.52, 95% CI: 1.33 ~ 1.73) than adequate GWG [ 12 ]. Furthermore, EGWG is regarded as an independent risk factor for macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational weight gain (GWG) has been shown to be associated with macrosomia and large for gestational age (LGA) infants [ 10 , 11 ]. Individual participant data from a meta-analysis revealed that excessive gestational weight gain (EGWG) was related to a greater risk of macrosomia (RR = 1.52, 95% CI: 1.33 ~ 1.73) than adequate GWG [ 12 ]. Furthermore, EGWG is regarded as an independent risk factor for macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate GWG can occur regardless of baseline nutritional status, even among those well-nourished before pregnancy [ 14 ]. Inadequate GWG increases the risks of LBW [ 14 17 ], prematurity [ 14 , 16 , 18 ], SGA births [ 14 , 15 , 17 , 18 ], and neonatal and infant death [ 19 , 20 ]. A meta-analysis showed that antenatal BEP supplementation increased the weekly rate of gestational weight gain (GWG) by 21 g/week (95% CI 1.5 to 40.0) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity are major public health problems [ 10 ]. Their incidence in pregnant women has been associated with newborn prematurity, neonatal infections, and cardiovascular, respiratory, and neurological disorders [ 7 , 9 , 11 , 12 , 13 ], with a high prevalence in low- and middle-income countries [ 14 ]. Promoting nutritional education in pre- and postnatal care routines can prevent neurological disorders in newborns [ 7 , 9 , 15 ], and future compromised functions in children’s static and dynamic balance, appendicular coordination, sensitivity, and motor coordination [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity are major public health problems [10]. Their incidence in pregnant women has been associated with newborn prematurity, neonatal infections, and cardiovascular, respiratory, and neurological disorders [7,9,[11][12][13], with a high prevalence in low-and middle-income countries [14]. Promoting nutritional education in pre-and Figure 1.…”
Section: Introductionmentioning
confidence: 99%